Solve for t (t-3)(t-3)=0

Math
(t-3)(t-3)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
t-3=0
t-3=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
t-3=0
Add 3 to both sides of the equation.
t=3
t=3
The final solution is all the values that make (t-3)(t-3)=0 true.
t=3
Solve for t (t-3)(t-3)=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top